Karakteristik Penderita Penyakit Konjungtivitis pada Poliklinik Mata Rumah Sakit Umum Daerah Sanjiwani Gianyar - Ni Kadek Intan Vitaloka; Rima Kusuma Ningrum; Ni Wayan Sedani (Fakultas Ilmu Kedokteran dan Ilmu Kesehatan, Universitas Warmadewa, 2024)
Conjunctivitis is an acute or chronic inflammation of the conjunctiva caused by microbial invasion or an immunological response. Conjunctivitis is considered one of the eye diseases with a high incidence, including in Bali. The objective of this study is to analyze the characteristics based on age, gender, address, location of eye complaints, and symptoms in patients with conjunctivitis. The method used in this research is a retrospective descriptive design through a cross-sectional approach, which is a research design that only describes secondary data obtained from data collection at one time. The data obtained were then tabulated and processed using the Statistical Package for Social Science (SPSS) for Windows. The results of the conjunctivitis study at the Eye Polyclinic of Sanjiwani Gianyar Regional General Hospital from June 2022 to June 2023 showed that the most cases (46%) were at the age of ?40 years, the majority (63%) occurred in men, with (44.33%) the most common clinical symptoms is red eyes, (51%) the location of bilateral eye complaints and the highest (37%) in Gianyar sub-district. Conjunctivitis can occur in everyone, both males and females, and can be found in various age groups with varying symptoms in each individual.